The Earth Keepers Solid Waste Management Planning Program: A Collaborative Approach to Utilizing Aboriginal Traditional Knowledge and Western Science in Ontario - McGregor, Deborah (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2010)
AbstractBoth the 1987 “Brundtland Report”, and Chapter 26 of Agenda 21 (which emerged from the 1992 “Earth Summit”), formally recognized the role of Indigenous people in global sustainable development. Agenda 21 requires that Aboriginal values, traditional knowledge, and resource management practices are recognized and meaningfully involved in sustainable development undertakings; and that capacity-building in Aboriginal communities, based on the adaptation and exchange of traditional knowledge, is developed so as to increase the ability of Aboriginal peoples to participate in sustainable development. This paper documents the principles behind and development of a practical program aimed at meeting these two criteria head on. Funded by the Canadian government and developed by an Aboriginal corporation with western scientific expertise, the “Earth Keepers” program represents a significant move towards establishing a truly collaborative program with benefits for Aboriginal and non-Aboriginal constituents alike. While participants in the program recognize areas for improvement, key among the program’s successful strategies to date has been the meaningful inclusion of Aboriginal community partners from the outset. The program’s built-in feedback system allows it to adapt to better meet the needs of participants over time. Continued scrutiny of this program as it evolves is warranted as it represents a significant departure from outmoded “colonial” approaches to research and development in Aboriginal communities, and an innovative step towards an improved environmental future for all participants.